Efficacy of Bioactive Dressings Compared to Passive Dressings in Promoting Wound Healing in Diabetic Foot Ulcers: A Randomized Controlled Trial - Supansa Srisawat; Nattay Kittipong; Rungnapa Pimchanok; Nur Aisyah binti Hassan; Ain Syuhada binti Salleh; Indah Susanti; Asmat Burhan (Indonesian Science Media, 2025)
Background: Diabetic foot ulcers (DFU) are a major complication of diabetes, leading to significant morbidity, increased healthcare costs, and a higher risk of amputations. Traditional wound care methods, such as passive dressings, have limitations in promoting faster healing and infection control. Bioactive dressings, which include antimicrobial and regenerative components, have shown promise in improving wound healing outcomes in DFU patients, but robust evidence comparing their efficacy to passive dressings in clinical practice remains scarce. Purpose: To evaluate the efficacy of bioactive dressings compared to passive dressings in promoting wound healing in patients with diabetic foot ulcers. Method: A randomized controlled trial was conducted in a single center, enrolling 90 adults with chronic DFUs. Participants were randomly assigned to receive either bioactive dressings (n=45) or passive dressings (n=45) for a 3-month treatment period. Inclusion criteria included adults aged 18–75 years with DFUs of at least 6 weeks duration and Wagner grade 2 or higher ulcers. The primary outcome was wound size reduction, assessed at baseline, 1 month, 2 months, and 3 months. Secondary outcomes included wound depth, infection control, epithelialization, and granulation. Results: At 1 month, the bioactive dressing group showed a significantly greater reduction in wound size compared to the passive dressing group (mean reduction 45% vs. 30%, p=0.003). Bioactive dressings also demonstrated superior infection control (p<0.001) and promoted faster epithelialization (p=0.022) and granulation (p=0.015). The control group exhibited slower healing rates and less pronounced improvements in secondary outcomes. Conclusions: Bioactive dressings significantly improve wound healing, infection control, and tissue regeneration in patients with diabetic foot ulcers compared to passive dressings. These findings support the integration of bioactive dressings as an effective treatment option in DFU management, particularly in the early stages of wound healing. Further studies with longer follow-up are needed to assess long-term outcomes